2017
DOI: 10.1177/1053815117706524
|View full text |Cite
|
Sign up to set email alerts
|

Internalizing Behaviors and Hyperactivity/Inattention: Consequences for Young Struggling Readers, and Especially Boys

Abstract: Although evidence of negative associations between early literacy development and children’s behavior problems exists, the field still lacks an understanding of the complicated links between these two areas. Children’s gender has often not been included in much of the extant research as a potential moderating variable, yet gender differences may provide insights into the nuanced relationship between early literacy development and maladaptive behaviors. Results from the current study of 472 kindergarten and fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…The majority of participants within this pool of studies were male (87.2% of participants for whom this information reported). This finding is not surprising as females are more likely to display internalising behaviours than externalising, which are more readily identified (Garwood et al, 2017a; Poulou, 2015). Prior research has shown boys are more often the target of teachers’ attention, for both positive and negative reasons (Beaman et al, 2006; Rice and Yen, 2010).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The majority of participants within this pool of studies were male (87.2% of participants for whom this information reported). This finding is not surprising as females are more likely to display internalising behaviours than externalising, which are more readily identified (Garwood et al, 2017a; Poulou, 2015). Prior research has shown boys are more often the target of teachers’ attention, for both positive and negative reasons (Beaman et al, 2006; Rice and Yen, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…Young children formally identified with EBD require timely and effective intervention to prevent or ameliorate the negative effects of EBD (Garwood et al, 2017a; Mitchell et al, 2019). As such, federal policies (e.g.…”
Section: Identification Of Young Children With Ebdmentioning
confidence: 99%
“…Students with disabilities rated higher on depression, suicidal ideation, and narcissism. Prior research has confirmed students with disabilities are more depressed than their peers (Cullinan & Sabornie, 2004;Garwood et al, 2017;Maag & Reid, 2006;Nelson & Harwood, 2011;Van Loan et al, 2019) and more at risk for suicide (McMillan & Jarvis, 2013). However, we are unaware of prior research indicating youth with disabilities rate higher on narcissism than their typically developing peers.…”
Section: Students With Disabilitiesmentioning
confidence: 87%
“…The co-occurrence of behavior problems and reading difficulties among many school-aged children has the attention of researchers (Roberts et al, 2019). One group of students who often struggle with reading and behavior problems are those with or at risk for EBD (Garwood et al, 2017), which typically includes students identified for special education services related to an emotional disturbance (ED) or a learning disability (LD; Forness et al, 2012). Children with or at risk for EBD demonstrate externalizing behaviors (e.g., aggression, noncompliance) and/or internalizing behaviors (e.g., depression, anxiety) and these characteristics can make it challenging for teachers to provide instruction and deliver intensive, research-based interventions (Wills et al, 2010).…”
Section: Co-occurrence Of Reading and Behavior Difficultiesmentioning
confidence: 99%